2011
DOI: 10.1007/s00412-011-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Homolog pairing and sister chromatid cohesion in heterochromatin in Drosophila male meiosis I

Abstract: Drosophila males undergo meiosis without recombination or chiasmata but homologous chromosomes pair and disjoin regularly. The X-Y pair utilizes a specific repeated sequence within the heterochromatic ribosomal DNA blocks as a pairing site. No pairing sites have yet been identified for the autosomes. To search for such sites, we utilized probes targeting specific heterochromatic regions to assay heterochromatin pairing sequences and behavior in meiosis by fluorescence in situ hybridization (FISH). We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 52 publications
5
47
0
Order By: Relevance
“…A recent fluorescent in situ hybridization (FISH) analysis, using probes to chromosome-specific repeated sequences, failed to detect any such stable pairing sites (i.e. sites that remain paired throughout meiosis I) in the heterochromatic regions of the major autosomes (Tsai et al, 2011), thus providing further evidence against PC-based pairing of the major autosomes. However, the small fourth chromosomes did remain paired at a specific heterochromatic site in >90% of spermatocytes throughout prophase I, suggesting that the fourth chromosome contains a PC.…”
Section: Autosomes In Drosophila Male Meiosismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent fluorescent in situ hybridization (FISH) analysis, using probes to chromosome-specific repeated sequences, failed to detect any such stable pairing sites (i.e. sites that remain paired throughout meiosis I) in the heterochromatic regions of the major autosomes (Tsai et al, 2011), thus providing further evidence against PC-based pairing of the major autosomes. However, the small fourth chromosomes did remain paired at a specific heterochromatic site in >90% of spermatocytes throughout prophase I, suggesting that the fourth chromosome contains a PC.…”
Section: Autosomes In Drosophila Male Meiosismentioning
confidence: 99%
“…Furthermore, recruitment of MNM, and perhaps SNM, to autosomes depends upon the Teflon (TEF) protein, which is required for segregation of the autosomes but not the sex chromosomes (Tomkiel et al, 2001;Thomas et al, 2005). We have suggested, by analogy to chiasmata in recombinational meiosis, that stable connections between autosomal homologs exist at different sites in different meiotic cells (Tsai et al, 2011). Time-lapse analyses in living spermatocytes using GFP-tagged chromosomal sites could be useful for revealing such stable connections; a stable connection site that happened to lie sufficiently close to a tagged chromosomal site should restrict the relative mobility of the tagged homologous alleles, perhaps dramatically so in favorable cases.…”
Section: Autosomes In Drosophila Male Meiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Given that rDNA loci are located on X and Y chromosomes (McKee et al, 2012), we hypothesized that X and Y centromeres associate with nucleoli and might aberrantly assemble CENP-A. Using fluorescent in situ hybridisation (FISH) probes specific for repeat sequences on the X (359 bp satellite) or Y (AATAC satellite) chromosomes (Tsai et al, 2011), and coimmunostaining for Fibrillarin, we confirmed that X and Y chromosomes associate with nucleoli in wild-type control and Cenp-C Z3-4375 /TM3 spermatocytes (Fig. 4A).…”
Section: And Y Centromeres At Nucleoli Assemble High Levels Of Cenpmentioning
confidence: 99%
“…However, our use of FISH probes to identify X and Y chromosomes, combined with antibody staining of endogenous CENP-A, could explain discrepancies between the two studies. It is also possible that the high CENP-A observed on sex chromosomes is sometimes due to their close association with the small fourth chromosome (Tsai et al, 2011), which is also located proximal to nucleoli. Interestingly, we find that in Cenp-C mutants the highly elevated CENP-A at X or Y centromeres is not retained past prophase I, i.e.…”
Section: Z3-4375mentioning
confidence: 99%